Grammar essentials - Dixson, Robert James (Longman, 2004)
Over 100 grammar points and more than 2,000 practice activities, making this new edition the ideal grammar review companion for any course including reading, writing and listening/speaking, as well as integrated skills. Students of all abilities can practice and review the critical grammar skills they need to achieve fluency in English